The association between triglyceride glucose-body Mass Index and in vitro fertilization outcomes in women with polycystic ovary syndrome: a cohort study - Xin Li; Ting Luan; Yi Wei; JuanJuan Zhang; Chun Zhao; Xiufeng Ling (BMC, 2024)
Abstract Background Polycystic Ovary Syndrome (PCOS) is a common reproductive disorder that frequently affects fertility. The TyG-BMI (Triglyceride glucose-body mass) index is a newly explored parameter that may be linked to reproductive results in individuals with PCOS. Nevertheless, its connection with outcomes in In Vitro Fertilization (IVF) procedures remains uncertain. Methods This study included a total of 966 females who underwent IVF treatments for PCOS. At the baseline, the participants were categorized into four groups according to the quartiles of TyG-BMI measured prior to oocyte retrieval. Subsequently, the study compared the differences in clinical and laboratory outcomes among these four groups. Results Patients in higher TyG-BMI quartiles exhibited a decreased number of retrieved oocytes, 2PN embryos, and available/high-quality embryos (P < 0.05 for Q1-Q4). Additionally, the multivariable regression analysis revealed that individuals in the top quartile of TyG-BMI had a lower count of accessible embryos (β = -0.224, P = 0.257) and a decreased number of high-quality embryos (β = -0.352, P = 0.028) in comparison to those in the lowest quartile. Nevertheless, there were no notable variances detected in the rates of pregnancy or live births among these quartiles. Furthermore, a linear correlation was noted between the TyG-BMI index and the quantity of accessible embryos (P-non-linear = 0.6, P-overall < 0.001), along with high-quality embryos (P-nonlinear = 0.026, P-overall = 0.006). In contrast, there was no notable linear correlation found between the TyG-BMI index and the available embryo rate (P-nonlinear = 0.60, P-overall = 0.8). Conclusions The results of this research emphasize the notable correlation between TyG-BMI and IVF results in females diagnosed with PCOS. The interplay of insulin resistance and disorders of lipid metabolism may indeed play a pivotal role in influencing the assisted reproductive outcomes of patients with PCOS. Considering these findings, TyG-BMI proves to be a valuable indicator for exploring this potential association.